Molecular Characterization and Antibiotic Resistant Profiles of Campylobacter Species Isolated From Poultry and Diarrheal Patients in Southeastern China 2017–2019 - Zhang, Leyi; Li, Yi; Shao, Yongqiang; Hu, Yuqin; Lou, Huihuang; Chen, Xiaonan; Wu, Yuejin; Mei, Lingling; Zhou, Biao; Zhang, Xibin; Yao, Wenwu; Fang, Lei; et al. (Frontiers in Microbiology, 2020)
Campylobacter is a zoonotic pathogen that causes foodborne diarrheal illness globally. To better understand health risks in Southeastern China, Campylobacter spp. were surveyed in humans and representative poultry products over three years. Representative 195 isolates (n=148, Campylobacter jejuni; n=45, Campylobacter coli; n=2 Campylobacter hyointestinalis) were examined for genetic relatedness and antimicrobial susceptibility. Nearly all Campylobacter isolates (99.0%, 193/195) were resistant to at least one class of antimicrobials, and 45.6% (89/195) of the isolates exhibited multi-drug resistant. Genotypic analysis revealed high diversity among tested strains. Multilocus sequence typing (MLST) displayed 120 sequence types (STs) including 42 novel STs being added to the PubMLST international database. 62 STs belonged to 16 previously characterized clonal complexes (CCs), of which CC-21, CC-45, CC-464, CC-574, CC-353 and CC-828 were most frequently identified. In addition, pulsed-field gel electrophoresis (PFGE) fingerprinting resulted in 66 PFGE SmaI patterns among the 125 isolates, with eight patterns shared between human and poultry sources. Subtyping data did not correlate with antimicrobial resistance phenotypes. Taken together, this large-scale surveillance study highlights high antimicrobial resistance and molecular features of Campylobacter isolates in Southeastern China.